2018
DOI: 10.1007/s11239-018-1680-8
|View full text |Cite
|
Sign up to set email alerts
|

Four factor prothrombin complex concentrate for warfarin reversal in patients with left ventricular assist devices

Abstract: Continuous flow left ventricular assist devices (CF-LVAD) require therapeutic anticoagulation which is often interrupted for procedures or bleeding. Prior to the availability of four factor prothrombin complex concentrate (4F-PCC) in the United States, warfarin was held and its effects reversed by vitamin K or fresh frozen plasma. We evaluated the use of 4F-PCC for temporary warfarin reversal in patients with CF-LVADs and assessed outcomes. This analysis is a retrospective study of CF-LVAD patients who receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Our study agrees with previous findings on PCC safety of use in cases where warfarin reversal was needed or use due to excessive post-OP bleeding (7)(8)(9). However, in our cohort the patient population that was supported by a short term LVAD was different, they were younger and usually supported due to an acute event thus making them an INTERMACS 1 profile type of patient; while age was not shown to be a risk factor for thrombosis in the literature, INTERMACS 1 patient profile was (10).…”
Section: Discussionsupporting
confidence: 92%
“…Our study agrees with previous findings on PCC safety of use in cases where warfarin reversal was needed or use due to excessive post-OP bleeding (7)(8)(9). However, in our cohort the patient population that was supported by a short term LVAD was different, they were younger and usually supported due to an acute event thus making them an INTERMACS 1 profile type of patient; while age was not shown to be a risk factor for thrombosis in the literature, INTERMACS 1 patient profile was (10).…”
Section: Discussionsupporting
confidence: 92%
“…7 Despite its rising popularity, few studies have reported indications and outcomes with use of 4F-PCC, and those that do focus on niche patient populations or specific dosing regimens. [9][10][11] In our study, we describe use of 4F-PCC in the emergency department at a large, suburban academic center to elucidate practice patterns.…”
Section: Introductionmentioning
confidence: 99%
“… Rapid INR reduction in 55% of the PCC group vs 10% of the FFP group Kerebel, 2012 37 Prospective, randomized, open-label study 59 VKA-associated intracranial hemorrhage 4F-PCC 40 IU.kg -1 of 4F-PCC significantly decreased the INR compared to that of the 25 IU.kg -1 group ( p = 0.001). Demeyere, 2010 55 Prospective, randomized, open-label, clinical study 40 cardiac surgery patients 4F-PCC vs FFP Faster target INR with PCC ( p = 0.007), and less additional dose ( p < 0.001) Burburry 2011 33 Prospective single-arm clinical study 178 presurgical patients under warfarin Vitamin K 94% with INR levels 1.5 or less on the day of surgery Chausson, 2018 41 Pilot clinical study 26 acute ischemic stroke patients 4F-PCC and vitamin K No symptomatic ICH or thrombotic events Pautas, 2011 34 Prospective, observational study 239 elderly hospitalized patients with over-anticoagulation Vitamin K Decrease in INR levels, achieving 2.7 ± 1.3 on Day 1 ( p < .0001) Bhatia, 2010 32 Prospective, observational study 45 proximal hip fracture patients Vitamin K INR levels decreased to 1.5 or less in 2 days (mean, 38 h; range, 15–64 h Rimsans, 2018 42 Prospective, observational study 37 patients with continuous flow left ventricular assistive devices 4F-PCC Efficient reversal, no case of thromboembolism, mean INR from 2.9 to 1.7 (p < 0.0001) …”
Section: Resultsmentioning
confidence: 99%
“…Prospective, randomized clinical trials show the clinical efficacy of 4-factor PCC in the reversal of warfarin as being superior to that of FFP in patients presenting VKA-related ICH 40 and achieving faster homeostasis in patients needing reversal for surgical interventions. 30 A retrospective observational study demonstrated the efficacy and safety of warfarin reversal using 4-factor PCC and vitamin K in acute ischemic stroke patients before undergoing intravenous thrombolysis; 41 in patients with continuous flow left ventricular assistive devices presenting bleeding or the need for urgent surgery, with no thromboembolic event observed; 42 in patients with intracranial bleeding requiring urgent neurosurgical intervention; 43 and in patients undergoing early orthopedic surgery (within 24 hours) due to hip fractures. 44 In an observational study of 143 patients on warfarin, the use of 4-factor PCC was safe as a reversal agent mainly for bleeding and prior to surgery, with 5 cases of thromboembolic complications.…”
Section: Resultsmentioning
confidence: 99%